2021
DOI: 10.1521/soco.2021.39.4.526
|View full text |Cite
|
Sign up to set email alerts
|

When the Going Gets Tough, How Do We Perceive the Future?

Abstract: People struggle to stay motivated to work toward difficult goals. Sometimes the feeling of difficulty signals that the goal is important and worth pursuing; other times, it signals that the goal is impossible and should be abandoned. In this article, we argue that how difficulty is experienced depends on how we perceive and experience the timing of difficult events. We synthesize research from across the social and behavioral sciences and propose a new, integrated model to explain how components of time percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…It has been a long time since we humans encountered such public health challenges; death anxiety brought from the unexpected COVID-19 pandemic indeed damaged individuals’, and especially medical staff’s, mental health and psychological well-being [ 25 ]. However, the present findings showed that during a pandemic, feeling anxiety from life scarcity would enhance the thinking about the meaning of life, which may further help medical staff pull through and achieve their goals [ 80 ]. Additionally, understanding what personality traits may help buffer detrimental outcomes has unique implications for individuals.…”
Section: Discussionmentioning
confidence: 99%
“…It has been a long time since we humans encountered such public health challenges; death anxiety brought from the unexpected COVID-19 pandemic indeed damaged individuals’, and especially medical staff’s, mental health and psychological well-being [ 25 ]. However, the present findings showed that during a pandemic, feeling anxiety from life scarcity would enhance the thinking about the meaning of life, which may further help medical staff pull through and achieve their goals [ 80 ]. Additionally, understanding what personality traits may help buffer detrimental outcomes has unique implications for individuals.…”
Section: Discussionmentioning
confidence: 99%